Sovereignty, Synecdoche, and the Prosthetic Hand in King John. (2nd January 2016) - Griffiths, Huw
Abstract : The word "hand" appears more times in King John than in any other Shakespeare play. The focus in Shakespeare's history plays on bodies and body parts allows for the central questions of sovereign relations to be asked over and over again: on whose behalf does a person act and to whom does their body belong? King John construes the political relations of early modern sovereignty through the "hand." This article argues that this construal allows the play to critique sovereign agency, representing it through synecdoche and understanding sovereign agency as a form of prosthesis.